Questions & Answers

Question

Answers

Answer

Verified

92.4k+ views

Let us assume a circle having Centre at O and radius equal to r. This circle is having two equal chords AB and CD having a length equal to x. From O, two perpendiculars OE and OF are drawn to chords AB and CD. Let us denote the length of OE = d and the length of OF = d'.

In circles, we have a property that if we draw a perpendicular from the Centre of the circle to any of its chord, these perpendicular divides the chord into two equal parts. From this property in the figure above, we can say AE = BE = DF = CF = $\dfrac{x}{2}$ ………………. (1)

In the question, we have to prove equal chords of a circle are equidistant from the Centre. So, we have to find the lengths of perpendicular distance OE and OF.

To find these lengths, we will use Pythagoras theorem which, the relation between the base, perpendicular and the hypotenuse of a right-angle triangle ABC is given by,

${\left( {{\text{AC}}} \right)^{\text{2}}}{\text{ = }}{\left( {{\text{AB}}} \right)^{\text{2}}}{\text{ + }}{\left( {{\text{BC}}} \right)^{\text{2}}}$………………… (2)

Applying Pythagoras theorem from equation (2) in triangle OEB, we get,

$\Rightarrow$${\left( {{\text{OB}}} \right)^{\text{2}}}{\text{ = }}{\left( {{\text{OE}}} \right)^{\text{2}}}{\text{ + }}{\left( {{\text{EB}}} \right)^{\text{2}}}$

Since, OB is the radius of the circle, OB = r.

And also, from (1), we have EB = $\dfrac{x}{2}$. Substituting in the above equation we get,

$\Rightarrow$${\left( r \right)^{\text{2}}}{\text{ = }}{\left( {{\text{OE}}} \right)^{\text{2}}}{\text{ + }}{\left( {\dfrac{x}{2}} \right)^{\text{2}}}$

$\Rightarrow$${\left( {{\text{OE}}} \right)^{\text{2}}}{\text{ = }}{{\text{r}}^{\text{2}}}{\text{ - }}\dfrac{{{{\text{x}}^{\text{2}}}}}{{\text{4}}}$

$\Rightarrow$$\left( {{\text{OE}}} \right){\text{ = }}\sqrt {{{\text{r}}^{\text{2}}}{\text{ - }}\dfrac{{{{\text{x}}^{\text{2}}}}}{{\text{4}}}} $………………….. (3)

Applying Pythagoras theorem from equation (2) in triangle OFC, we get,

$\Rightarrow$${\left( {{\text{OC}}} \right)^{\text{2}}}{\text{ = }}{\left( {{\text{OF}}} \right)^{\text{2}}}{\text{ + }}{\left( {{\text{FC}}} \right)^{\text{2}}}$

Since, OB is the radius of the circle, OC = r.

And also, from (1), we have FC = $\dfrac{x}{2}$. Substituting in the above equation we get

$\Rightarrow$${\left( r \right)^{\text{2}}}{\text{ = }}{\left( {{\text{OF}}} \right)^{\text{2}}}{\text{ + }}{\left( {\dfrac{x}{2}} \right)^{\text{2}}}$

$\Rightarrow$${\left( {{\text{OF}}} \right)^{\text{2}}}{\text{ = }}{{\text{r}}^{\text{2}}}{\text{ - }}\dfrac{{{{\text{x}}^{\text{2}}}}}{{\text{4}}}$

$\Rightarrow$$\left( {{\text{OF}}} \right){\text{ = }}\sqrt {{{\text{r}}^{\text{2}}}{\text{ - }}\dfrac{{{{\text{x}}^{\text{2}}}}}{{\text{4}}}} $………………….. (4)

From equation (3) and equation (4), we get,

$\Rightarrow$OE = OF